RNase T2 in Inflammation and Cancer: Immunological and Biological Views - Wu, Lei; Xu, Yanquan; Zhao, Huakan; Li, Yongsheng (Frontiers in Immunology, 2020)
The distribution and level of nucleic acids are regulated by ribonucleases, which are critical for the pathophysiology of inflammation and cancer. RNase T2 is highly conserved in mammals, which preferentially cleaves single-stranded RNA molecules between purine and uridine residues to generate two nucleotide fragments with 2’3’-cyclophosphine adenosine/guanosine terminus and uridine residue, respectively. These products are constitute agonistic ligands for the first and second binding pockets of TLR8 to effectively activate TLR8, which is critical in resisting bacterial infections. RNase T2 is detected in all tissues in human, especially in immune cells. It includes both intracellular and secretory forms and display differential roles on endogenous and exogenous RNA. In this review, we introduce the distribution and expression pattern of RNase T2, its differential roles in inflammation and cancer, and the perspective on its research and related application in medicine.